(untitled) (Maslahah: Journal of Islamic Studies, 2024)
This study aims to evaluate the effectiveness of the application of the crossword puzzle learning approach in improving students’ understanding of the Pillars of Islam material at SD Ula Cipayung. Through classroom actions in three cycles, namely pre-cycle, cycle 1, and cycle 2, focusing on corrective actions through the application of the crossword puzzle method, researchers found that the use of this method significantly improved student learning outcomes. It can be seen from the increase in the average pre-test score of students in the pre-cycle is 65, in cycle 1 the average score of the post-test increased to 78 (an increase of 11.43%), and in cycle 2 the average score of the post-test increased to 85 (an increase of 9.09%). In addition, students’ mastery of the material also increased significantly, with the understanding of shahada increasing from 70% to 95%. So, crossword puzzle learning is effective in improving student learning outcomes in Islamic Religious Education subjects.